New Pedagogical Technologies in Teaching Foreign Languages - Karamatovna, Ravshanova Nasiba (Researchparks Publishing, 2023)
This article deals with the problem of finding new techniques and ways to increase motivation for learning foreign languages. One of these forms is new pedagogical technologies, the introduction of which contributes to the effective learning of the language. The article defines the concepts of